Open Inguinal Hernia Model - Anthony Vigil (Association of American Medical Colleges, 2010)
Abstract The open tension-free inguinal hernia repair is a well-established method for repairing inguinal hernias. This technique has a low-recurrence rate with minimal morbidity. As has been shown with laparoscopic hernia repairs, adequate training is needed to decrease the length of the learning curve. We have developed a training model that surgical residents can use to practice their technique of tension-free inguinal hernia repairs. The aim was to develop a model that would familiarize training surgeons with the difficult anatomy of the groin and the steps needed to complete the tension-free hernia repair, in order to shorten the time needed to master this skill. The hernia model can be used for training residents and students in the technique of inguinal hernia repair using mesh. It can also be available during groin anatomy cadaver teaching sessions. The open hernia repair model should shorten the learning curve of performing acceptable open tension-free inguinal hernia repairs. It is durable, cost effective, and easy to use.